Mitigation Co-benefits of Ecosystem-Based Adaptation Measures: Learnings from Catalyzing Ecosystem Restoration for Climate-Resilient Natural Capital and Rural Livelihoods in Degraded Forests and Rangelands of Nepal - Khanal, Keshav Prasad; Khatri, Top Bahadur; Nepal, Santosh Mani; Poudel, Buddi Sagar; Sapkota, Raju; Thapa, Binod; Dahal, Digambar Singh; Dhakal, Bhola (Banko Janakari, 2025)
Ecosystem-based Adaptation (EbA) interventions, while primarily aimed at enhancing resilience to climate impacts, can also produce measurable climate mitigation benefits. This study evaluates the carbon sequestration and emission reduction potential of EbA interventions implemented in degraded forests and rangelands of Nepal to quantify their climate mitigation outcomes. Carbon sequestration was estimated using secondary data from national sources and literature for two types of interventions: reforestation of 1,393 hectares and Sustainable Forest Management (SFM) over 10,000 hectares. Standardized carbon stock increments from similar ecological zones were applied over 20 years. Reforested areas sequestered an average of 83.4 tons of CO2 per hectare per year, while sustainably managed forests contributed 4.4 tons of CO2 per hectare per year. Over 20 years, these measures are projected to sequester approximately 1,134 t CO2/ha from plantations and 533 t CO2/ha from SFM. EbA interventions in Nepal not only build adaptive capacity but also provide significant climate mitigation benefits. The observed carbon gains highlight the importance of incorporating ecosystem restoration into national climate policies, especially in forest and rangeland landscapes where adaptation and mitigation collaborations can be achieved.